Systematic Literature Review: Transformation of Islamic Higher Education Institutions (Examination of Ontology, Epistemology, and Axiology) - Sopian Lubis; Salminawati Salminawati; Usiono Usiono (Universitas Muhammadiyah Enrekang, 2023)
The dichotomy of knowledge is the main problem of Islamization and integration of knowledge in the concept of Islamic education. In essence, Islam does not recognize the division of knowledge, but it cannot be denied that in its history there have been explanations about knowledge that are obligatory ain and obligatory kifayah. This is the spirit of Islamic higher education institutions to carry out institutional transformations, curricula, to the level of application in the context of life. The change in status from STAIN/IAIN to UIN is an inevitability that has been going on since the 2000s. The aim of the article is to find philosophical concepts (ontology, epistemology and axiology) in the transformation of Islamic Religious Higher Education institutions (PTKIN). The method used is a systematic literature review (SLR) with the Preferred Reporting Items for Systematic and Meta-Analyses (PRISMA) approach. The data sources for this article are journals and articles related to the topic of discussion via Google Scholar and then extracted to be used as discussion material. The results obtained are the freedom for State Islamic higher education institutions to innovate in institutions, faculties and curricula in order to create a UIN that can integrate Religious and General Sciences through the policies of the Indonesian Ministry of Religion.